2021
DOI: 10.1093/molbev/msab211
|View full text |Cite
|
Sign up to set email alerts
|

Nemertean, Brachiopod, and Phoronid Neuropeptidomics Reveals Ancestral Spiralian Signaling Systems

Abstract: Neuropeptides are diverse signalling molecules in animals commonly acting through G-protein coupled receptors (GPCRs). Neuropeptides and their receptors underwent extensive diversification in bilaterians and the relationships of many peptide-receptor systems have been clarified. However, we lack a detailed picture of neuropeptide evolution in lophotrochozoans as in-depth studies only exist for molluscs and annelids. Here we analyse peptidergic systems in Nemertea, Brachiopoda and Phoronida. We screened transcr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 124 publications
4
49
0
Order By: Relevance
“…Through the sequence comparison and phylogenetic analysis, here we report that Hdh-NPFR-related receptors are belong to the NPF/Y receptor family distinct from the sNPFR and PrRP-R families in bilaterians. Consistent with this analysis, recent phylogenetic studies with novel NPF/NPY/PrRP/sNPF-related receptors in echinoderms and three lophotrochozoans (nemerteans, brachiopods, and phoronids) have revealed that all the examined molluscan NPFR-like sequences are orthologous to the vertebrate NPY receptors 22 , 43 . In addition, we suggest that Hdh-NPFR is most likely similar to vertebrate NPYR2 among the three vertebrate NPYR ancestors, the progenitors of the NPYR1, NPYR2, and NPYR5 subfamilies 4 , 50 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Through the sequence comparison and phylogenetic analysis, here we report that Hdh-NPFR-related receptors are belong to the NPF/Y receptor family distinct from the sNPFR and PrRP-R families in bilaterians. Consistent with this analysis, recent phylogenetic studies with novel NPF/NPY/PrRP/sNPF-related receptors in echinoderms and three lophotrochozoans (nemerteans, brachiopods, and phoronids) have revealed that all the examined molluscan NPFR-like sequences are orthologous to the vertebrate NPY receptors 22 , 43 . In addition, we suggest that Hdh-NPFR is most likely similar to vertebrate NPYR2 among the three vertebrate NPYR ancestors, the progenitors of the NPYR1, NPYR2, and NPYR5 subfamilies 4 , 50 .…”
Section: Discussionsupporting
confidence: 73%
“…In-depth screening of databases of diverse bilaterian genome and transcriptome sequences strongly suggested an ancient co-evolutionary history between NP precursor and receptor genes 42 , 43 . Elucidation of the endogenous ligands for orphan receptors in D. melanogaster and C. elegans has also offered important insight into the origin of NP signaling systems, dating back to the emergence of protostomes 44 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Identification of 3 MIP-R subtypes in bivalves and their absence from other protostomes suggests that they emerged prior to the divergence of the ecdysozoan and lophotrochozoan lineages (Figure 3). The protostome RGWaR, FMRFaR, ProctR and MyoR that are proposed to have radiated from the same common ancestor as MIP-R/AST-BRs were included in phylogenetic tree (15,16,79) and the tree topology confirmed that all receptors shared a common origin with the orphan deuterostome GPR139/142 (15,16).…”
Section: Mip-rmentioning
confidence: 88%
“…For the trees of the AST-Rhodopsin b family GPCRs the related protostome receptors from the FMRFamide (FMRFaR), RGWamide (RGWaR), Proctolin (ProctR) and Myosupressin/ Myomodulin (MyoR) families were also included as well as the vertebrate sequence orthologues GPR142 and GPR139 from H. s a p i e n s ( G P R 1 4 2 , N P _ 0 0 1 3 1 8 0 0 5 . 1 a n d G P R 1 3 9 , NP_001002911.1) and L. oculeatus (GPR142, XP_006635495 and GPC139, XP_006637109) (15,16,79).…”
Section: Sequence Comparisons and Phylogenetic Analysismentioning
confidence: 99%
“…Neuropeptides are neuronally secreted peptides that regulate diverse physiological and behavioral processes in animals, with their effects on target cells/tissues typically mediated by G protein–coupled receptors ( 1 ). Investigation of the phylogenetic distribution of neuropeptides and their cognate receptors has revealed that the evolutionary origin of over 30 neuropeptide signaling systems can be traced back to the urbilaterian common ancestor of protostomes and deuterostomes ( 2 6 ). Important insights into neuropeptide evolution have been obtained from nonchordate deuterostome invertebrates (e.g., echinoderms), which occupy an “intermediate” phylogenetic position with respect to chordates and protostomes ( 4 , 7 , 8 ).…”
mentioning
confidence: 99%